THEMED ISSUE – Variations and innovations in care and care work: Critical perspectives. (1st June 2018) - Christensen, Karen; Chou, Yueh-Ching
Abstract : Welcome to this themed issue on 'Variations and innovations in care and care work: critical perspectives', which we think provides new and interesting knowledge about some of the important changes taking place in different parts of the world regarding formal (publicly organised) care services, 'informal' care work within families and networks, and the relationship between formal and informal care. Two central changes triggering the development of variations and innovations are the demographic issue of a worldwide ageing population and the idea, related to welfare services in general, of changing the role of welfare users from mere 'receivers' of help to more 'responsibilised' and/or independent users.